2016
DOI: 10.1371/journal.pone.0152419
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Sources of Emotional Distress among People Living with Scleroderma: A Focus Group Study

Abstract: BackgroundSystemic sclerosis, or scleroderma, is a chronic and rare connective tissue disease with negative physical and psychological implications. Sources of emotional distress and the impact they have on the lives of people with scleroderma are not well understood.ObjectivesTo gain an in-depth understanding of the emotional experiences and sources of emotional distress for women and men living with scleroderma through focus group discussions.MethodsThree semi-structured focus group discussions were conducte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 34 publications
1
18
0
Order By: Relevance
“…psoriasis and atopic dermatitis) has reported lower health-related quality of life (HRQoL) 7 and negative impacts on psychosocial functioning. 8,9 The rarity of morphoea poses particular challenges with respect to gaps in knowledge about its aetiology, prognosis and treatment [10][11][12] and also about the HRQoL of individuals with this disorder. 13 To date, little has been written on HRQoL in paediatric patients with morphoea, specifically facial subtypes.…”
Section: What Does This Study Add?mentioning
confidence: 99%
See 1 more Smart Citation
“…psoriasis and atopic dermatitis) has reported lower health-related quality of life (HRQoL) 7 and negative impacts on psychosocial functioning. 8,9 The rarity of morphoea poses particular challenges with respect to gaps in knowledge about its aetiology, prognosis and treatment [10][11][12] and also about the HRQoL of individuals with this disorder. 13 To date, little has been written on HRQoL in paediatric patients with morphoea, specifically facial subtypes.…”
Section: What Does This Study Add?mentioning
confidence: 99%
“…The rarity of morphoea poses particular challenges with respect to gaps in knowledge about its aetiology, prognosis and treatment and also about the HRQoL of individuals with this disorder . To date, little has been written on HRQoL in paediatric patients with morphoea, specifically facial subtypes .…”
mentioning
confidence: 99%
“…Previous research has flagged understanding of SSc and its consequences as well as personal control and emotional representations as the main differences in perceptions between patients and rheumatologists or general practitioners [ 8 ]. Studies have also indicated that patients feel physicians are dismissive of their concerns regarding topics such as leisure and social activities, sexuality or parenting [ 9 , 14 ]. We found that patients mainly provided information that physicians were seeking, and felt intimidated or embarrassed about asking questions related to managing symptoms and how this affects their working life or their relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Findings from this study are consistent with other studies of physician-patient communication within consultations and their impact on emotional well-being. Both a lack of empathy from HCPs and their unwillingness to discuss aspects not specifically related to SSc have previously been cited by patients as a great source of emotional distress [17]. Additionally, patient's dissatisfaction has been shown to relate to the absence of a holistic approach to care and due to a lack of tact by physicians, who they felt had little interest in their suffering [13].…”
Section: Discussionmentioning
confidence: 99%